Implementing climate menu labels in university settings: a narrative review - Hey, Mei-Li; Crespi, Elizabeth; Yett, Ariana; Altema-Johnson, Daphene; Wolfson, Julia; Ramsing, Rebecca (Frontiers in Nutrition, 2025)
Global food systems are a major contributor to climate change, accounting for more than 30% of greenhouse gas emissions (GHGEs). This review synthesizes current evidence on the potential of climate labels (which we define as labels attached to menus or food items with climate impact information) in university dining settings to encourage climate-friendly food decisions. In April 2024, we searched Scopus, ProQuest, Web of Science, and PubMed using developed terms related to climate labels and universities. We identified 280 articles and narrowed down the review to 14 articles based on study setting, language, and scope. Of the 14 studies, 86% (12 articles) observed a decrease in the consumption of foods researchers classified as high emissions, 60% (8 articles) observed a decrease in the consumption of foods classified as medium-emission foods, and 63% (9 articles) observed an increase in the consumption of foods classified as low-emission food. Effects varied by gender and age, with women appearing to experience a greater response to the climate labels, but no observable differences were evident by ethnicity or socio-economic class. Studies that supplemented climate labeling initiatives with sales promotions or resources encouraging consumers to conduct their own emission research also saw favorable results. The studies suggest a small yet detectable shift in consumer behavior in response to climate labels in university dining settings; however, further research is needed on: (1) improving climate label effectiveness, (2) the effect of climate labels among different demographic attributes (e.g., income, ethnicity), and (3) the long-term and spillover effects of the labels on the healthiness of consumer diets, and institutional sourcing practices.